Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

Atrial fibrillation in an African-American cohort: The Jackson Heart Study. - Austin, Thomas R; Wiggins, Kerri L; Blackshear, Chad; Yang, Yi; Benjamin, Emelia J; Curtis, Lesley H; Sotoodehnia, Nona; Correa, Adolfo; Heckbert, Susan R (Clin Cardiol, 2018)
BACKGROUND: Atrial fibrillation (AF) is an important public health problem across race/ethnic groups. Data from US cohort studies initiated in the 1980s suggest a higher prevalence of AF risk factors among African-Americans (AAs) than whites, but lower AF incidence. The Jackson Heart Study (JHS) is a community-based study of 5306 AAs recruited starting in 2000. HYPOTHESIS: Demographic, anthropometric, cardiovascular, and/or electrocardiographic factors are associated with AF incidence in JHS. METHODS: Using baseline participant characteristics and incident AF identified through hospital surveillance, study electrocardiogram, and Medicare claims, we estimated age- and sex-specific AF incidence rates, compared them with rates in AA participants in the Multi-Ethnic Study of Atherosclerosis (MESA) and Cardiovascular Health Study (CHS), and examined associations of cardiovascular risk factors with AF. RESULTS: A total of 66 participants had prevalent AF at baseline. Over an average follow-up of 8.5 years, 242 cases of incident AF were identified. Age- and sex-specific AF incidence rates in JHS were similar to those among AAs in MESA and appeared slightly lower than those among AAs in CHS. In an age- and sex-adjusted model, associations with incident AF were observed for modifiable risk factors: high body weight (HR = 1.23 per 15 kg, 95%CI 1.13-1.35), systolic blood pressure (HR = 1.29 per 20 mmHg, 95%CI 1.13-1.47), and current smoking (HR = 1.80, 95%CI 1.27-2.55). Risk estimates associated with these risk factors were only slightly attenuated after multivariable adjustments. CONCLUSIONS: These findings underscore the potential additional benefits of interventions for weight management, control of hypertension, and smoking cessation for the prevention of AF among AAs.

Genome-wide analyses identify as a susceptibility locus for premature atrial contraction frequency. - Thériault, Sébastien; Imboden, Medea; Biggs, Mary L; Austin, Thomas R; Aeschbacher, Stefanie; Schaffner, Emmanuel; Brody, Jennifer A; Bartz, Traci M; Risch, Martin; Grossmann, Kirsten; Lin, Henry J; Soliman, Elsayed Z; et al. (iScience, 2022)
Premature atrial contractions (PACs) are frequently observed on electrocardiograms and are associated with increased risks of atrial fibrillation (AF), stroke, and mortality. In this study, we aimed to identify genetic susceptibility loci for PAC frequency. We performed a genome-wide association study meta-analysis with PAC frequency obtained from ambulatory cardiac monitoring in 4,831 individuals of European ancestry. We identified a genome-wide significant locus at the gene. The lead variant, rs7373862, located in an intron of , was associated with an increase of 0.12 [95% CI 0.08-0.16] standard deviations of the normalized PAC frequency per risk allele. Among genetic variants previously associated with AF, there was a significant enrichment in concordance of effect for PAC frequency (n = 73/106, p = 5.1 × 10). However, several AF risk loci, including , were not associated with PAC frequency. These findings suggest the existence of both shared and distinct genetic mechanisms for PAC frequency and AF.

Plasma proteomic signature of decline in gait speed and grip strength. - Liu, Xiaojuan; Pan, Stephanie; Xanthakis, Vanessa; Vasan, Ramachandran S; Psaty, Bruce M; Austin, Thomas R; Newman, Anne B; Sanders, Jason L; Wu, Chenkai; Tracy, Russell P; Gerszten, Robert E; Odden, Michelle C (Aging Cell, 2022)
The biological mechanisms underlying decline in physical function with age remain unclear. We examined the plasma proteomic profile associated with longitudinal changes in physical function measured by gait speed and grip strength in community-dwelling adults. We applied an aptamer-based platform to assay 1154 plasma proteins on 2854 participants (60% women, aged 76 years) in the Cardiovascular Health Study (CHS) in 1992-1993 and 1130 participants (55% women, aged 54 years) in the Framingham Offspring Study (FOS) in 1991-1995. Gait speed and grip strength were measured annually for 7 years in CHS and at cycles 7 (1998-2001) and 8 (2005-2008) in FOS. The associations of individual protein levels (log-transformed and standardized) with longitudinal changes in gait speed and grip strength in two populations were examined separately by linear mixed-effects models. Meta-analyses were implemented using random-effects models and corrected for multiple testing. We found that plasma levels of 14 and 18 proteins were associated with changes in gait speed and grip strength, respectively (corrected p < 0.05). The proteins most strongly associated with gait speed decline were GDF-15 (Meta-analytic p = 1.58 × 10 ), pleiotrophin (1.23 × 10 ), and TIMP-1 (5.97 × 10 ). For grip strength decline, the strongest associations were for carbonic anhydrase III (1.09 × 10 ), CDON (2.38 × 10 ), and SMOC1 (7.47 × 10 ). Several statistically significant proteins are involved in the inflammatory responses or antagonism of activin by follistatin pathway. These novel proteomic biomarkers and pathways should be further explored as future mechanisms and targets for age-related functional decline.
Keywords: Adult; Female; Gait; Hand Strength; Humans; Independent Living; Male; Proteomics; Walking Speed

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer's disease (AD) and AD related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from nine diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5 to 20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs. ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed Mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (Beta=0.04; 95% CI 0.02, 0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the US. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.

Late-life plasma proteins associated with prevalent and incident frailty: A proteomic analysis. - Liu, Fangyu; Austin, Thomas R; Schrack, Jennifer A; Chen, Jingsha; Walston, Jeremy; Mathias, Rasika A; Grams, Morgan; Odden, Michelle C; Newman, Anne; Psaty, Bruce M; Ramonfaur, Diego; Shah, Amil M; et al. (Aging Cell, 2023)
Proteomic approaches have unique advantages in the identification of biological pathways that influence physical frailty, a multifactorial geriatric syndrome predictive of adverse health outcomes in older adults. To date, proteomic studies of frailty are scarce, and few evaluated prefrailty as a separate state or examined predictors of incident frailty. Using plasma proteins measured by 4955 SOMAmers in the Atherosclerosis Risk in Community study, we identified 134 and 179 proteins cross-sectionally associated with prefrailty and frailty, respectively, after Bonferroni correction (p < 1 × 10 ) among 3838 older adults aged ≥65 years, adjusting for demographic and physiologic factors and chronic diseases. Among them, 23 (17%) and 82 (46%) were replicated in the Cardiovascular Health Study using the same models (FDR p < 0.05). Notably, higher odds of prefrailty and frailty were observed with higher levels of growth differentiation factor 15 (GDF15; p  = 1 × 10 , p  = 2 × 10 ), transgelin (TAGLN; p  = 2 × 10 , p  = 6 × 10 ), and insulin-like growth factor-binding protein 2 (IGFBP2; p  = 5 × 10 , p  = 1 × 10 ) and with a lower level of growth hormone receptor (GHR, p  = 3 × 10 , p  = 2 × 10 ). Longitudinally, we identified 4 proteins associated with incident frailty (p < 1 × 10 ). Higher levels of triggering receptor expressed on myeloid cells 1 (TREM1), TAGLN, and heart and adipocyte fatty-acid binding proteins predicted incident frailty. Differentially regulated proteins were enriched in pathways and upstream regulators related to lipid metabolism, angiogenesis, inflammation, and cell senescence. Our findings provide a set of plasma proteins and biological mechanisms that were dysregulated in both the prodromal and the clinical stage of frailty, offering new insights into frailty etiology and targets for intervention.

Plasma Proteomic Associations With Incident Ischemic Stroke in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Psaty, Bruce M; Elkind, Mitchell S V; Floyd, James S; Gerszten, Robert E; Shojaie, Ali; Heckbert, Susan R; Bis, Joshua C; Austin, Thomas R; Tirschwell, David L; Delaney, Joseph A C; et al. (Neurology, 2023)
BACKGROUND: Plasma proteomics may elucidate novel insights into the pathophysiology of ischemic stroke (IS), identify biomarkers of IS risk, and guide development of nascent prevention strategies. We evaluated the relationship between the plasma proteome and IS risk in the population-based Cardiovascular Health Study (CHS). METHODS: Eligible CHS participants were free of prevalent stroke and underwent quantification of 1298 plasma proteins using the aptamer-based SOMAScan assay platform from the 1992-1993 study visit. Multivariable Cox proportional hazards regression was used to evaluate associations between a 1-standard deviation increase in the log-2 transformed estimated plasma protein concentrations and incident IS, adjusting for demographics, IS risk factors, and estimated glomerular filtration rate. For proteins independently associated with incident IS, a secondary stratified analysis evaluated associations in subgroups defined by sex and race. Exploratory analyses evaluated plasma proteomic associations with cardioembolic and non-cardioembolic IS as well as proteins associated with IS risk in participants with left atrial dysfunction but without atrial fibrillation. RESULTS: Of 2983 eligible participants, the mean age was 74.3 (± 4.8) years, 61.2% were women, and 15.4% were Black. Over a median follow-up of 12.6 years, 450 participants experienced an incident IS. N-terminal pro-brain natriuretic peptide (NTproBNP, adjusted HR 1.37, 95% CI 1.23-1.53, P=2.08x10) and macrophage metalloelastase (MMP12, adjusted HR 1.30, 95% CI 1.16-1.45, P=4.55x10) were independently associated with IS risk. These two associations were similar in men and women and in Black and non-Black participants. In exploratory analyses, NTproBNP was independently associated with incident cardioembolic IS, E-selectin with incident non-cardioembolic IS, and secreted frizzled-related protein 1 with IS risk in participants with left atrial dysfunction. CONCLUSIONS: In a cohort of older adults, NTproBNP and MMP12 were independently associated with IS risk. We identified plasma proteomic determinants of incident cardioembolic and non-cardioembolic IS and found a novel protein associated with IS risk in those with left atrial dysfunction.

A proteomic analysis of atrial fibrillation in a prospective longitudinal cohort (AGES-Reykjavik study). - Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Austin, Thomas R; Frick, Elisabet A; Axelsson, Gisli T; Launer, Lenore; Psaty, Bruce M; Loureiro, Joseph; Orth, Anthony P; Aspelund, Thor; Emilsson, Valur; Floyd, James S; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF) is associated with high risk of comorbidities and mortality. Our aim was to examine causal and predictive relationships between 4137 serum proteins and incident AF in the prospective population-based Age, Gene/Environment Susceptibility-Reykjavik (AGES-Reykjavik) study. METHODS AND RESULTS: The study included 4765 participants, of whom 1172 developed AF. Cox proportional hazards regression models were fitted for 4137 baseline protein measurements adjusting for known risk factors. Protein associations were tested for replication in the Cardiovascular Health Study (CHS). Causal relationships were examined in a bidirectional, two-sample Mendelian randomization analysis. The time-dependent area under the receiver operating characteristic curve (AUC)-statistic was examined as protein levels and an AF-polygenic risk score (PRS) were added to clinical risk models. The proteomic signature of incident AF consisted of 76 proteins, of which 63 (83%) were novel and 29 (38%) were replicated in CHS. The signature included both N-terminal prohormone of brain natriuretic peptide (NT-proBNP)-dependent (e.g. CHST15, ATP1B1, and SVEP1) and independent components (e.g. ASPN, AKR1B, and LAMA1/LAMB1/LAMC1). Nine causal candidates were identified (TAGLN, WARS, CHST15, CHMP3, COL15A1, DUSP13, MANBA, QSOX2, and SRL). The reverse causal analysis suggested that most AF-associated proteins were affected by the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide improved the prediction of incident AF events close to baseline with further improvements gained by the AF-PRS at all time points. CONCLUSION: The AF proteomic signature includes biologically relevant proteins, some of which may be causal. It mainly reflects an NT-proBNP-dependent consequence of the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide is a promising marker for incident AF in the short term, but risk assessment incorporating a PRS may improve long-term risk assessment.
Keywords: Atrial Fibrillation; Biomarkers; Endosomal Sorting Complexes Required for Transport; Humans; Natriuretic Peptide, Brain; Oxidoreductases Acting on Sulfur Group Donors; Peptide Fragments; Prognosis; Prospective Studies; Proteomics; Risk Factors

Proteomic prediction of incident heart failure and its main subtypes. - Emilsson, Valur; Jonsson, Brynjolfur G; Austin, Thomas R; Gudmundsdottir, Valborg; Axelsson, Gisli T; Frick, Elisabet A; Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Loureiro, Joseph; Brody, Jennifer A; Aspelund, Thor; Launer, Lenore J; et al. (Eur J Heart Fail, 2023)
AIM: To examine the ability of serum proteins in predicting future heart failure (HF) events, including HF with reduced or preserved ejection fraction (HFrEF or HFpEF), in relation to event time, and with or without considering established HF-associated clinical variables. METHODS AND RESULTS: In the prospective population-based Age, Gene/Environment Susceptibility Reykjavik Study (AGES-RS), 440 individuals developed HF after their first visit with a median follow-up of 5.45 years. Among them, 167 were diagnosed with HFrEF and 188 with HFpEF. A least absolute shrinkage and selection operator regression model with nonparametric bootstrap were used to select predictors from an analysis of 4782 serum proteins, and several pre-established clinical parameters linked to HF. A subset of 8-10 distinct or overlapping serum proteins predicted different future HF outcomes, and C-statistics were used to assess discrimination, revealing proteins combined with a C-index of 0.80 for all incident HF, 0.78 and 0.80 for incident HFpEF or HFrEF, respectively. In the AGES-RS, protein panels alone encompassed the risk contained in the clinical information and improved the performance characteristics of prediction models based on NT-proBNP and clinical risk factors. Finally, the protein predictors performed particularly well close to the time of an HF event, an outcome that was replicated in the Cardiovascular Health Study (CHS). CONCLUSION: A small number of circulating proteins accurately predicted future HF in the AGES-RS cohort of older adults, and they alone encompass the risk information found in a collection of clinical data. Incident HF events were predicted up to eight years, with predictor performance significantly improving for events occurring less than one year ahead, a finding replicated in an external cohort study. This article is protected by copyright. All rights reserved.

Circulating Blood Plasma Profiling Reveals Proteomic Signature and a Causal Role for SVEP1 in Sudden Cardiac Death. - Duong, ThuyVy; Austin, Thomas R; Brody, Jennifer A; Shojaie, Ali; Battle, Alexis; Bader, Joel S; Hong, Yun Soo; Ballantyne, Christie M; Coresh, Josef; Gerszten, Robert E; Tracy, Russell P; Psaty, Bruce M; et al. (Circ Genom Precis Med, 2024)

Human Plasma Proteomic Profile of Clonal Hematopoiesis. - Yu, Zhi; Vromman, Amélie; Nguyen, Ngoc Quynh H; Schuermans, Art; Rentz, Thiago; Vellarikkal, Shamsudheen K; Uddin, Md Mesbah; Niroula, Abhishek; Griffin, Gabriel; Honigberg, Michael C; Lin, Amy E; Gibson, Christopher J; et al. (bioRxiv, 2024)
Plasma proteomic profiles associated with subclinical somatic mutations in blood cells may offer novel insights into downstream clinical consequences. Here, we explore such patterns in clonal hematopoiesis of indeterminate potential (CHIP), which is linked to several cancer and non-cancer outcomes, including coronary artery disease (CAD). Among 61,833 ancestrally diverse participants (3,881 with CHIP) from NHLBI TOPMed and UK Biobank with blood-based DNA sequencing and proteomic measurements (1,148 proteins by SomaScan in TOPMed and 2,917 proteins by Olink in UK Biobank), we identified 32 and 345 unique proteins from TOPMed and UK Biobank, respectively, associated with the most prevalent driver genes (, , and ). These associations showed substantial heterogeneity by driver genes, sex, and race, and were enriched for immune response and inflammation pathways. Mendelian randomization in humans, coupled with ELISA in hematopoietic -/- vs wild-type mice validation, disentangled causal proteomic perturbations from CHIP. Lastly, we identified plasma proteins shared between CHIP and CAD.

Large-scale circulating proteome association study (CPAS) meta-analysis identifies circulating proteins and pathways predicting incident hip fractures. - Austin, Thomas R; Fink, Howard A; Jalal, Diana I; Törnqvist, Anna E; Bůzková, Petra; Barzilay, Joshua I; Lu, Tianyuan; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Hveem, Kristian; Jonasson, Christian; et al. (J Bone Miner Res, 2024)
Hip fractures are associated with significant disability, high cost, and mortality. However, the exact biological mechanisms underlying susceptibility to hip fractures remain incompletely understood. In an exploratory search of the underlying biology as reflected through the circulating proteome, we performed a comprehensive Circulating Proteome Association Study (CPAS) meta-analysis for incident hip fractures. Analyses included 6430 subjects from two prospective cohort studies (Cardiovascular Health Study and Trøndelag Health Study) with circulating proteomics data (aptamer-based 5 K SomaScan version 4.0 assay; 4979 aptamers). Associations between circulating protein levels and incident hip fractures were estimated for each cohort using age and sex-adjusted Cox regression models. Participants experienced 643 incident hip fractures. Compared with the individual studies, inverse-variance weighted meta-analyses yielded more statistically significant associations, identifying 23 aptamers associated with incident hip fractures (conservative Bonferroni correction 0.05/4979, P < 1.0 × 10-5). The aptamers most strongly associated with hip fracture risk corresponded to two proteins of the growth hormone/insulin growth factor system (GHR and IGFBP2), as well as GDF15 and EGFR. High levels of several inflammation-related proteins (CD14, CXCL12, MMP12, ITIH3) were also associated with increased hip fracture risk. Ingenuity pathway analysis identified reduced LXR/RXR activation and increased acute phase response signaling to be overrepresented among those proteins associated with increased hip fracture risk. These analyses identified several circulating proteins and pathways consistently associated with incident hip fractures. These findings underscore the usefulness of the meta-analytic approach for comprehensive CPAS in a similar manner as has previously been observed for large-scale human genetic studies. Future studies should investigate the underlying biology of these potential novel drug targets.

Large-Scale Proteomics Identifies Novel Biomarkers and Circulating Risk Factors for Aortic Stenosis. - Shelbaya, Khaled; Arthur, Victoria; Yang, Yimin; Dorbala, Pranav; Buckley, Leo; Claggett, Brian; Skali, Hicham; Dufresne, Line; Yang, Ta-Yu; Engert, James C; Thanassoulis, George; Floyd, James; et al. (J Am Coll Cardiol, 2024)
BACKGROUND: Limited data exist regarding risk factors for aortic stenosis (AS). The plasma proteome is a promising phenotype for discovery of novel biomarkers and potentially causative mechanisms. OBJECTIVES: The aim of this study was to discover novel biomarkers with potentially causal associations with AS. METHODS: We measured 4,877 plasma proteins (SomaScan aptamer-affinity assay) among ARIC (Atherosclerosis Risk In Communities) study participants in mid-life (visit 3 [V3]; n = 11,430; age 60 ± 6 years) and in late-life (V5; n = 4,899; age 76 ± 5 years). We identified proteins cross-sectionally associated with aortic valve (AV) peak velocity (AVmax) and dimensionless index by echocardiography at V5 and with incident AV-related hospitalization after V3 with the use of multivariable linear and Cox proportional hazard regression. We assessed associations of candidate proteins with changes in AVmax over 6 years and with AV calcification with the use of cardiac computed tomography, replicated analysis in an independent sample, performed Mendelian randomization, and evaluated gene expression in explanted human AV tissue. RESULTS: Fifty-two proteins cross-sectionally were associated with AVmax and dimensionless index at V5 and with risk of incident AV-related hospitalization after V3. Among 3,413 participants in the Cardiovascular Health Study, 6 of those proteins were significantly associated with adjudicated moderate or severe AS, including matrix metalloproteinase 12 (MMP12), complement C1q tumor necrosis factor-related protein 1 (C1QTNF1), and growth differentiation factor-15. MMP12 was also associated with greater increase in AVmax over 6 years, greater degree of AV calcification, and greater expression in calcific compared with normal or fibrotic AV tissue. C1QTNF1 had consistent potential causal effects on both AS and AVmax according to Mendelian randomization analysis. CONCLUSIONS: These findings identify MMP12 as a potential novel circulating biomarker of AS risk and C1QTNF1 as a new putative target to prevent AS progression.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Calcinosis; Humans; Matrix Metalloproteinase 12; Middle Aged; Proteomics; Risk Factors

A plasma protein-based risk score to predict hip fractures. - Austin, Thomas R; Nethander, Maria; Fink, Howard A; Törnqvist, Anna E; Jalal, Diana I; Bůzková, Petra; Barzilay, Joshua I; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Lu, Tianyuan; Hveem, Kristian; et al. (Nat Aging, 2024)
As there are effective treatments to reduce hip fractures, identification of patients at high risk of hip fracture is important to inform efficient intervention strategies. To obtain a new tool for hip fracture prediction, we developed a protein-based risk score in the Cardiovascular Health Study using an aptamer-based proteomic platform. The proteomic risk score predicted incident hip fractures and improved hip fracture discrimination in two Trøndelag Health Study validation cohorts using the same aptamer-based platform. When transferred to an antibody-based proteomic platform in a UK Biobank validation cohort, the proteomic risk score was strongly associated with hip fractures (hazard ratio per s.d. increase, 1.64; 95% confidence interval 1.53-1.77). The proteomic risk score, but not available polygenic risk scores for fractures or bone mineral density, improved the C-index beyond the fracture risk assessment tool (FRAX), which integrates information from clinical risk factors (C-index, FRAX 0.735 versus FRAX + proteomic risk score 0.776). The developed proteomic risk score constitutes a new tool for stratifying patients according to hip fracture risk; however, its improvement in hip fracture discrimination is modest and its clinical utility beyond FRAX with information on femoral neck bone mineral density remains to be determined.

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

Association of PM With Cardiac Mechanics Using Speckle-Tracking Echocardiography in the Cardiovascular Health Study. - Chang, Andrew Y; Kaufman, Joel D; Tan, Annabel Xulin; Shah, Sanjiv J; Patel, Ravi B; Margolis, Helene; Psaty, Bruce M; Gardin, Julius M; Al-Kindi, Sadeer; Austin, Thomas R; Odden, Michelle C (JACC Cardiovasc Imaging, 2025)

The impact of common and rare genetic variants on bradyarrhythmia development. - Weng, Lu-Chen; Rämö, Joel T; Jurgens, Sean J; Khurshid, Shaan; Chaffin, Mark; Hall, Amelia Weber; Morrill, Valerie N; Wang, Xin; Nauffal, Victor; Sun, Yan V; Beer, Dominik; Lee, Simon; et al. (Nat Genet, 2025)
To broaden our understanding of bradyarrhythmias and conduction disease, we performed common variant genome-wide association analyses in up to 1.3 million individuals and rare variant burden testing in 460,000 individuals for sinus node dysfunction (SND), distal conduction disease (DCD) and pacemaker (PM) implantation. We identified 13, 31 and 21 common variant loci for SND, DCD and PM, respectively. Four well-known loci (SCN5A/SCN10A, CCDC141, TBX20 and CAMK2D) were shared for SND and DCD, while others were more specific for SND or DCD. SND and DCD showed a moderate genetic correlation (r = 0.63). Cardiomyocyte-expressed genes were enriched for contributions to DCD heritability. Rare-variant analyses implicated LMNA for all bradyarrhythmia phenotypes, SMAD6 and SCN5A for DCD and TTN, MYBPC3 and SCN5A for PM. These results show that variation in multiple genetic pathways (for example, ion channel function, cardiac developmental programs, sarcomeric structure and cellular homeostasis) appear critical to the development of bradyarrhythmias.
Keywords: Bradycardia; Cardiac Conduction System Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Pacemaker, Artificial; Phenotype; Polymorphism, Single Nucleotide; Sick Sinus Syndrome

Plasma Proteomic Assessment of Calcific Aortic Valve Disease in Older Adults. - Bortnick, Anna E; Austin, Thomas R; Hamerton, Emily; Gudmundsdottir, Valborg; Emilsson, Valur; Jennings, Lori L; Gudnason, Vilmundur; Owens, David S; Massera, Daniele; Dufresne, Line; Yang, Ta-Yu; Engert, James C; et al. (J Am Heart Assoc, 2025)
BACKGROUND: Calcific aortic valve disease (CAVD), and ensuing severe aortic stenosis (AS), is the foremost valvular disorder of aging, yet preventive therapies are lacking. A better understanding of the molecular underpinnings of aortic valve calcification (AVC) is necessary to develop pharmacologic interventions. METHODS AND RESULTS: We undertook large-scale plasma proteomics in a cohort study of adults ≥65 years old, the CHS (Cardiovascular Health Study), to identify individual proteins associated with echocardiographic AVC and incident moderate/severe AS. Proteomics measurements were performed with the aptamer-based SomaLogic platform of ~5000 proteins. Significant proteins were validated in a second cohort, the AGES-RS (Age, Gene/Environment Susceptibility-Reykjavik Study), which assessed AVC and AS by computed tomography. The potential causal associations of replicated proteins were tested in 2-sample Mendelian randomization using identified cis protein quantitative trait loci in consortia having computed tomography-quantified AVC or AS as outcomes. Six proteins showed Bonferroni-corrected significant relationships with AVC in CHS. Three of these, CXCL-12 (C-X-C chemokine ligand 12), KLKB1 (kallikrein), and leptin, replicated in AGES-RS, of which the former 2 are novel. Only 1 protein, CXCL6, which showed a near-significant association with AS in the replication cohort, was significantly (positively) associated with incident AS. Mendelian randomization analysis was conducted for KLKB1, CXCL12, and CXCL6, which supported a causal relationship for higher KLKB1 with lower AVC (beta=-0.25, =0.009). CONCLUSIONS: This study of older adults newly identified and largely replicated associations of 3 circulating proteins with calcific aortic valve disease, of which the relationship of plasma KLKB1 may have a causal basis. Additional investigation is necessary to determine if KLKB1 could be harnessed for calcific aortic valve disease therapeutics.
Keywords: Age Factors; Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Blood Proteins; Calcinosis; Chemokine CXCL12; Echocardiography; Female; Humans; Male; Mendelian Randomization Analysis; Proteomics; Severity of Illness Index

Whole genome sequence association analysis of brain structural volume measures in the NHLBI TOPMed Program highlights novel loci in diverse participants. - Shade, Lincoln Mp; Sharifitabar, Mohsen; Beiser, Alexa; Satizabal, Claudia L; Mosley, Thomas H; Curran, Joanne E; Bressler, Jan; Heckbert, Susan R; Hughes, Timothy M; Austin, Thomas R; Nasrallah, Ilya M; Launer, Lenore J; et al. (medRxiv, 2025)
Brain structural volumes are highly heritable and are linked to multiple neuropsychological outcomes, including Alzheimer's disease (AD). Genome-wide association studies have successfully identified genetic variants associated with intracranial volume (ICV), total brain volume (TBV), hippocampal volume (HV), and lateral ventricular volume (LVV). However, these studies mostly focused on common genetic variants with minor allele frequencies (MAF) > 1%, and individuals included in most of these studies were of predominantly European ancestry. Here, we performed whole-genome sequence (WGS) association studies of MRI brain volumes in 7,674 individuals of diverse race and ethnicity from the Trans-Omics for Precision Medicine (TOPMed) program. We identified novel genetic loci on chromosomes 13 and 16 near and associated with HV and TBV, respectively (lead variants rs115674829, -value = 1.7×10 in pooled analysis and rs150440001, -value = 6.6×10 in black participants). Both lead variant minor A alleles are rarer in white participants (MAF = 0.14% and 0.03%) and in Hispanic participants (MAF = 1.5% and 0.17%) but more common in black participants (MAF = 13% and 1.5%). Rare variant aggregated analyses identified a gene encoding a kinase involved in neuroinflammation and promising target for AD treatment, suggestively associated with LVV (-value=5×10). This study provides new insights into the genetic correlates of brain structural volumes and illustrates the importance of leveraging WGS data and cohorts of diverse race and ethnicity to better characterize the genetic architecture of complex polygenic traits.